A Comparative Study between Commercial Arbitration and Sports Arbitration - Hamza E. Albaheth; Ashraf M. A. Elfakharani (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This paper offers a thorough evaluation of the similarities and differences between sports arbitration and commercial arbitration, with a focus on the procedural distinctions between the two methods of arbitration. The paper examines the details, time constraints, regulations regarding admissible evidence, and protocols for reaching a verdict in each instance. It is crucial to shed light on these differences in order to assist the practitioners and stakeholders involved in sports and business disputes. This research seeks to offer a comprehensive understanding of the unique characteristics, procedures, and challenges that differentiate sports arbitration and commercial arbitration in their respective domains. For this research, a normative qualitative method is employed to thoroughly examine and analyse various legal resources, including published works, arbitration rules, awards, and cases. This ensures that both sports arbitration and commercial arbitration are practical in order to effectively coordinate the use of the normative qualitative technique. The study sheds light on the difficulties encountered in the realms of commercial and sports arbitration, including concerns about the enforceability of awards, the matter of confidentiality, and challenges arising from dominance. The paper also provides a detailed account of the established best practices in each of the domains. The study also explores the significant substantive and procedural distinctions between commercial and sports arbitration. It specifically examines aspects such as legal systems, timeframes, rules of evidence, the selection of arbitrators, and the roles of governing bodies. The conclusion offers a concise overview of the main discoveries of the study and the key distinctions and similarities between commercial and sports arbitration. Practitioners and policymakers will find valuable recommendations in addition to a discussion on future research directions.